Trade-off scenario analysis: Highlights from SHiFT Work Package 4 - CGIAR (CGIAR, 2024)
While transforming food systems toward sustainable healthy diets will produce many positive outcomes, challenges could arise throughout the process. Identifying the trade-offs of food systems transformation helps stakeholders prepare for different outcomes, informing policies and interventions that can minimize negative effects. Learn how the CGIAR Research Initiative on Sustainable Healthy Diets through Food Systems Transformation (SHiFT)is using simulation modeling to assess trade-off scenarios in this video featuring Michiel van Dijk, SHiFT Work Package 4 Lead.